Can society be commodities all the way down? Post-Polanyian reflections on capitalist crisis - Fraser, Nancy (Economy and Society, 2014)
In his classic 1944 book, The great transformation, Karl Polanyi traced the roots of capitalist crisis to efforts to create ‘self-regulating markets’ in land, labour and money. The effect was to turn those three fundamental bases of social life into ‘fictitious commodities’. The inevitable result, Polanyi claimed, was to despoil nature, rupture communities and destroy livelihoods. This diagnosis has strong echoes in the twenty-first century: witness the burgeoning markets in carbon emissions and biotechnology; in child-care, schooling and the care of the old; and in financial derivatives. In this situation, Polanyi's idea of fictitious commodification affords a promising basis for an integrated structural analysis that connects three dimensions of the present crisis: the ecological, the social and the financial. This paper explores the strengths and weaknesses of Polanyi's idea.
Keywords: capitalist crisis; commodification; domination; double movement; fictitious commodities